Enhanced mechanical properties of boron nitride nanosheet/copper nanocomposites via a molecular-level mixing process. (15th August 2020) - Yoo, Sung Chan; Kim, Joonhui; Lee, Wonki; Hwang, Jun Yeon; Ryu, Ho Jin; Hong, Soon Hyung
Abstract: Boron nitride nanosheet/copper (BNNS/Cu) nanocomposites were fabricated using a molecular-level mixing process. This process was facilitated by electrostatic interactions between negatively charged functional groups on the BNNSs and Cu metal precursor ions. The mixing process induced the formation of oxygen (O)-mediated bonding between BNNSs and the Cu matrix, which enabled enhanced dispersion of BNNSs and interfacial bonding with the Cu matrix. The mechanical properties of the resulting nanocomposite material, including the yield strength, tensile strength, and modulus, were greatly improved with incorporation of only a small amount of BNNSs using the molecular-level mixing process. The strengthening effect of BNNSs was attributed to a combination of a small contribution from grain size refinement effect and a major contribution from load transfer effect. This extraordinary load transfer strengthening, supported by modeling, is attributed to O-mediated interfacial bonding between the BNNSs and Cu. High-resolution transmission electron microscopy revealed the formation of an amorphous interphase between the BNNSs and the Cu matrix. This O-rich phase may have contributed to the strengthening effect of the BNNSs. The BNNS/Cu nanocomposite showed excellent high-temperature mechanical properties. These superior mechanical properties of the nanocomposite material suggest applications in various structural materials, including those requiring exposure to high temperatures.